PENGARUH KESADARAN MEREK RITEL, ASOSIASI MEREK RITEL, KUALITAS YANG DITERIMA MEREK RITEL, KESETIAAN MEREK RITEL TERHADAP EKUITAS MEREK RITEL (Studi Empiris pada Kartika Sari) - Ongky Alex Sander; Fahrul Riza (Business Management Journal, 2016)
This study examined the antecendets of Customer Based Retail Brand Equity (CBRE) such as retail brand awareness, retail brand association, retail brand perceived quality and retail brand loyalty on retail brand equity. Results of testing the hypothesis (t-test) found that variables retail brand awareness and retail brand association does not significantly influence on retail brand equity. While the other variables are retail brand perceived quality and retail brand loyalty has significantly influence on retailer brand equity.Retail brand perceived quality and retail brand loyalty must be considered by the retail businesses because it has a greater influence in creating the Retail Brand Equity (RBE). For further research, can develop research models such as the effect of brand building activities to the comunity identificatiion retailer with retail customer based equity as a mediating variableKeywords: Customer Based Retail Brand Equity (CBRE), retail brand association, retail brand perceived quality and retail brand loyalty on retail brand equity